Discovery and development of SV2A PET tracers: Potential for imaging synaptic density and clinical applications. (November 2017) - Mercier, Joel; Provins, Laurent; Valade, Anne
Abstract : Imaging synaptic density in vivo has promise for numerous research and clinical applications in the diagnosis and treatment monitoring of neurodegenerative and psychiatric diseases. Recent developments in the field of PET, such as SV2A human imaging with the novel tracers UCB-A, UCB-H and UCB-J, may help in realizing this potential and bring significant benefit for the patients suffering from these diseases. This review provides an overview of the most recent progress in the field of SV2A PET imaging, its potential for use as a biomarker of synaptic density and the future development areas.